Method of Building a Model of Operational Changes for the Marine Combustion Engine Describing the Impact of the Damages of This Engine on the Characteristics of Its Operation Process - Landowski Bogdan; Pająk Michał; Żółtowski Bogdan; Muślewski Łukasz (Polish Maritime Research, 2017)
This article deals with the modeling of the processes of operating both marine main and auxiliary engines. The paper presents a model of changes in operating conditions of ship’s internal combustion engine. The semi-Markov decision process was used to mathematically describe the process model of the engine. The developed model describes the effect of engine damage on the characteristics of its operation. A change in the input parameters of the model can simulate the influence of internal and external factors on the course of the analyzed process. A simplified calculation example is also presented for illustration purposes. The presented method together with developed algorithms and IT tools can be used to solve a wide range of problems related to the operation of marine main engines and other marine equipment as well as maritime and port facilities. This concerns primarily the economic, risk management and operational security issues of complex technical systems, as well as the readiness and reliability analysis of technical facilities.